76.6k views
0 votes
Write each expression without the radical.

open the picture.

Write each expression without the radical. open the picture.-example-1
User Fatou
by
5.7k points

1 Answer

5 votes

Answer:

Part 1)
4m^{(1)/(2)}

Part 2)
3(r)^{(1)/(3)}(s)^{(2)/(3)}(t)^{(4)/(3)}

Part 3)
3(x)^{(9)/(4)}

Explanation:

Part 1) Write each expression without the radical.

we have


√(16m)

we know that


16=4^2

substitute


√(4^2m)

Remember that


\sqrt[a]{x^b}=x^{(b)/(a)}


(x^a)^(b)=x^(ab)

so


√(4^2m)=(4^2m)^{(1)/(2)}=(4^2)^{(1)/(2)}(m)^{(1)/(2)}=4m^{(1)/(2)}

Part 2) Write each expression without the radical.

we have


\sqrt[3]{27rs^2t^4}

we know that


27=3^3

substitute


\sqrt[3]{3^3rs^2t^4}

Remember that


\sqrt[a]{x^b}=x^{(b)/(a)}


(x^a)^(b)=x^(ab)

so


\sqrt[3]{3^3rs^2t^4}=(3^3rs^2t^4)^{(1)/(3)}=(3^3)^{(1)/(3)}(r)^{(1)/(3)}(s^2)^{(1)/(3)}(t^4)^{(1)/(3)}=3(r)^{(1)/(3)}(s)^{(2)/(3)}(t)^{(4)/(3)}

Part 3) Write each expression without the radical.

we have


\sqrt[4]{81x^9}

we know that


81=3^4

substitute


\sqrt[4]{3^4x^9}

Remember that


\sqrt[a]{x^b}=x^{(b)/(a)}


(x^a)^(b)=x^(ab)

so


\sqrt[4]{3^4x^9}=(3^4x^9)^{(1)/(4)}=(3^4)^{(1)/(4)}(x^9)^{(1)/(4)}=3(x)^{(9)/(4)}

User Emonz
by
4.9k points